Indian renaissance: the Modi decade - Edited by Pandit, Aishwarya (Chennai Westland, 2024)
This book is a COMPREHENSIVE OVERVIEW OF TEN YEARS OF THE MODI GOVERNMENT. A collection of essays that cover the whole gamut of social, cultural and political change across India during the last ten years, Indian Renaissance brings together diverse voices: senior journalists, political leaders, policymakers and public intellectuals. They examine the singular influence of Modi and his transformation of the BJP, and the development initiatives that have changed the lives of Indians even in the remotest of villages. There are essays on India$1 (Bs relationship with other nations, especially the US, and on the newly revived relations between India and the Arab world. Yet others reflect on the digital revolution, the challenge of educating a billion people, and the new (intern)nationalist paradigm that is being given shape by the government of India.s
Keywords: Politics and Government; Prime Minister; Political Ideology